Pure Erythroid Leukaemia- Report of An Extremely Rare Case with Dismal Prognosis (Journal of Bangladesh College of Physicians and Surgeons, 2021)
Pure erythroid leukaemia (PEL) is a rare and aggressive form of acute leukaemia whose biology remains poorly characterized. The category of acute erythroid leukaemia was signiûcantly revised in the 2016 revision to the World Health Organization (WHO) classiûcation of myeloid neoplasms. In the previous 2008 WHO classiûcation, acute erythroid leukaemia was categorized into two subtypes: erythroleukaemia and pure erythroid leukaemia (PEL), whereas in the 2016 WHO update, erythroleukaemia was merged into myelodysplastic syndrome and PEL becomes the only type of acute erythroid leukaemia. De novo pure erythroid leukaemia is a disease of adults (median age 68 years), exhibits a striking male predominance, is universally associated with an abnormal karyotype and has an exceedingly poor overall median survival of 1.4 months. Given the limited number of reports of this rare and diagnostically challenging entity, we report clinicopathologic characteristics of a case of PEL, diagnosis was made by the bone marrow morphology and immunophenotyping.J Bangladesh Coll Phys Surg 2021; 39: 266-268